The preferred Learning style and its relationship to intelligence and habits of study among students of basic education in science - Hussien, Payman Sabr; Haso , Ashqi Suleman (Zanco Journal of Human Sciences, 2021)
The researcher conducted a study under the title " The preferred Learning style and its relationship to intelligence and habits of study among students of basic education in science ". The aim of the research is to discover the relationship that may link the preferred Learning style and both intelligence and study habits of female students of basic education in science. The researchers used the descriptive approach to achieve the research goals. The sample of the research consisted of (68) female students at Kashbeen School for Girls in Erbil Governorate, whose ages ranged between (14-15) years. To achieve the research objectives, the researchers used the following tools collecting data: 1- The preferred Learning style. 2- Raven's Sequence Matrix Test. 3- Scale of study habits. The data were statistically analyzed by using the SPSS statistical program and it reached the following conclusions: 1- found a negative correlation and statistically significant relationship between the preferred Learning style (cooperative style) and intelligence among students of basic education in science. 2- found a positive correlation and statistically significant relationship between the preferred Learning style (individual style) and intelligence among students of basic education in science. 3- found a positive correlation and statistically significant relationship between the preferred Learning style (competitive style) and intelligence among students of basic education in science. 4- There was a statistically significant negative correlation between the preferred Learning style (the cooperative style) and the habits of studying among students of basic education in science. 5- found a statistically positive correlation between the preferred Learning style (individual style) and the study habits of students of basic education in science. 6- There was a statistically significant negative correlation between the preferred Learning style (the competitive style) and the study habits of students of basic education in science.